السر آدابه وأحكامه في القرآن الكريم -دراسة موضوعية- - غريسي, ايمان (University of Eloued جامعة الوادي, 2018)
"الحمد لله رب العالمين والصلاة والسلام على أشرف الرسل نبينا محمد وآله وأصحابه. يعالج هذا الموضوع الموسوم بـ:""السّر آدابه وأحكامه في القرآن الكريم (دراسة موضوعية) دراسة مصطلح السرّ في القرآن الكريم دراسة موضوعية، وتتبع ألفاظه ومعانيه وسياقاته، ففي ما تمثلت الأحكام والآداب المستنبطة من آيات السّر؟ وللإجابة عن هذا السؤال بيّنت معنى السّر وأهم اشتقاقته وتصريفاته ثمّ استخرجت المفردات القريبة المعنى من السرّ و الوجوه والنظائر للفظة، وتركزت دراسة هذا الموضوع في تحديد سياقات اللفظة في القرآن الكريم والتي ارتكزت على ثلاث سياقات أساسية وهي: الآداب، سياق مخاطبة النبي ، سياق الأحكام الشرعية، واستخلصت من هذه ا بأنّ آداب السّر في القرآن الكريم متمثلة في آداب المعاشرة الزوجية، آداب كتمان السرّ، آداب التناجي العامة والخاصة، وأن أحكامه تمثلت في: أحكام صدقة السرّ أحكام صدقة المناجاة أحكام خطبة المرأة المعتدة. " "Praise be to Allah, the lord of the worlds, peace and blissings be upon ashraf the messengers of our prophet Muhammad and his companions and companions. This subject is addressed by: ""The secret of ethics and its rulings in the Holy Quran (objective study) Study of the term of the sacrament in the Holy Quran An objective study and follow its words, meanings and contexts, in what were the rulings and ethics derived from the secret verses? And its definitions and then extracted the words close to the meaning of the secret and faces And the analogies of the word, and focused on the study of this subject in determining the context of the word in the Holy Quran, which was based on three basic contexts namely: literature, the context of addressing the Prophet the context of the provisions of legitimacy, and concluded that the ethics of the secret in the Koran represented in the ethics of marital marriage, Confidentiality and public and private etiquette, and that its provisions were as follows: The provisions of the charity of the secret The provisions of the charity of invoking the provisions of the sermon of the oppressed woman. "
مذكرة ماستر تخصص تفسير وعلوم القرآن
Keywords: السّر ، القرآن الكريم، الأحكام الشرعية.; The secret, the Holy Quran, the legal rulings.